Perbandingan Rasio FEV1/FVC pada Mahasiswa Perokok Elektronik dan Perokok Tembakau - Korto, Feren E. I.; Sapulete, Ivonny M.; Pangkahila, Erwin A. (e-CliniC, 2025)
Abstract: Tobacco cigarettes and electronic cigarettes contain harmful and toxic chemicals for the body, leading to addiction and dependence on users. Long-term cigarette consumption causes health problems, especially in the respiratory system, marked by disturbances or decreases in lung function. One parameter for measuring lung function is the FEV1/FVC ratio. This study aimed to determine the difference in the FEV1/FVC ratio between electronic and tobacco smokers. This was an analytical and observational study with a cross-sectional design. Samples were students of the Faculty of Civil Engineering, Universitas Sam Ratulangi obtained by using purposive sampling. Data were analyzed using the Mann-Whitney non-parametric independent sample test. The results showed that out of 37 respondents who were electronic cigarette smokers, 33 respondents (89,2%) were in the normal category, and two respondents (5,4%) were in the mild to moderate category. Among tobacco cigarette smokers, out of 46 respondents, 45 respondents (97,8%) were in the normal category, and one respondent (2,2%) was in the moderate category. The Mann-Whitney test revealed a p-value of 0.107 (p>0.05) between the two groups. In conclusion. there is no significant difference in the FEV1/FVC ratio between electronic and tobacco smokers among students at the Faculty of Civil Engineering, Universitas Sam Ratulangi. Keywords: FEV1/FVC ratio; electronic cigarette smokers; tobacco smokers Abstrak: Rokok tembakau dan rokok elektronik mengandung bahan kimia berbahaya dan beracun bagi tubuh serta mengakibatkan adiksi dan dependensi pada penggunanya. Konsumsi rokok jangka panjang menyebabkan masalah kesehatan khususnya sistem pernapasan, ditandai gangguan atau penurunan fungsi paru. Salah satu parameter pengukuran kesehatan paru ialah rasio FEV1/FVC. Penelitian ini bertujuan untuk mengetahui perbedaan rasio FEV1/FVC pada perokok elektronik dan tembakau. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Sampel penelitian ialah mahasiswa Fakultas Teknik Sipil Universitas Sam Ratulangi, diperoleh dengan teknik purposive sampling. Alat yang digunakan untuk mengukur rasio FEV1/FVC ialah spirometer. Analisis data menggunakan uji beda sampel bebas non parametrik Mann-Whitney. Hasil penelitian mendapatkan total 37 responden jenis perokok elektronik; 33 responden (89,2%) kategori normal, dua responden (5,4%) kategori ringan - sedang. Perokok tembakau sebanyak total 46 responden; 45 responden (97,8%) kategori normal dan satu responden (2,2%) kategori sedang. Hasil uji Mann-Whitney mendapatkan nilai p=0,107 (p>0,05). Simpulan penelitian ini ialah tidak terdapat perbedaan bermakna antara rasio FEV1/FVC pada perokok elektronik dan perokok tembakau mahasiswa Fakultas Teknik Sipil Universitas Sam Ratulangi. Kata kunci: rasio FEV1/FVC; perokok elektronik; perokok tembakau